Therapeutic effects of resveratrol and Omega-3 in mice atherosclerosis: focus on histopathological changes - Shamsi Sadat Mosavi; Soghra Rabizadeh; Amirhossein Yadegar; Sara Seifouri; Fatemeh Mohammadi; Reihane Qahremani; Salome Sadat Salehi; Armin Rajab; Alireza Esteghamati; Manouchehr Nakhjavani (BMC, 2023)
Abstract Background Resveratrol and omega-3 have been shown to prevent atherosclerosis. However, histopathological changes and their comparison have not been studied well. This study investigated the therapeutic effects of resveratrol and omega-3 in experimental atherosclerosis of mice. Methods We divided sixty 6-week-old male C57BL/6 mice into six groups and followed for 10 weeks: (1) standard diet, (2) atherogenic diet, (3) atherogenic diet along with resveratrol from the start of the sixth week, (4) atherogenic diet along with omega-3 from the start of the sixth week, (5) standard diet along with resveratrol from the start of the sixth week, (6) standard diet along with omega-3 from the start of the sixth week. Results The mice fed on an atherogenic diet had a larger fat area and a thicker aortic wall thickness than mice fed on a standard diet. The use of omega-3 and resveratrol in the mice with an atherogenic diet resulted in a significantly reduced fat area (p-value = 0.003), and resveratrol had a significantly higher effect. Omega-3 or resveratrol induced a significant reduction in aortic wall thickness in mice on an atherogenic diet, and there was no significant difference between them. Among the mice with a standard diet, this study did not observe any significant changes in the fat area or the aortic wall thickness with the consumption of omega-3 or resveratrol. Conclusions Resveratrol and omega-3 had a regressive and therapeutic role in atherosclerosis, with a more significant effect in favor of resveratrol.